ANALISIS KEADAAN TERTENTU TENTANG PENERAPAN PIDANA MATI: STUDI KASUS KORUPSI BANSOS COVID-19 - Vavirotus Sholichah; Satria Unggul Wicaksana Prakasa (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Indonesia is still ranked 96th out of the 180 most corrupt countries in the world. This is evidenced by many corruption cases that occur, such as the corruption case of embezzlement of social assistance funds for PKH members in Malang, the corruption case that ensnared the inactive West Bandung Regent Aa Umbara, and the corruption case that made former Social Minister Juliari Batubara a suspect. The phrase